Curcumin Inhibits Apoptosis and Brain Edema Induced by Hypoxia-Hypercapnia Brain Damage in Rat Models. (June 2015) - Yu, Linsheng; Fan, Yanyan; Ye, Guanghua; Li, Junli; Feng, Xiangping; Lin, Kezhi; Dong, Miuwu; Wang, Zhenyuan
<x xml:space="preserve">Abstract</x> Abstract: Curcumin, extracted from South Asian spice turmeric, has been determined to have the promising ability in antioxidation and anti-inflammation. However, the effect of curcumin on treating brain damage has been not reported. In this article, the aim was to evaluate the effect of curcumin on cell apoptosis in rats exposed to hypoxia-hypercapnia and explore the therapeutic potential of curcumin in hypoxia-hypercapnia brain damage (HHBD). Sprague Dawley rats were randomly assigned into 3 groups: control group, hypoxia-hypercapnia group and curcumin group. The Fas/FasL expressions in HHBD rats treated by curcumin were measured by immunohistochemical staining and western blotting. The pathological changes of brain cells were observed by transmission electron microscope. Rats with HHBD showed significant increase of Fas/FasL expression and ultrastructural changes in brain tissue cells. Curcumin intervention effectively reversed the Fas/FasL-mediated apoptosis and HHBD-induced brain edema. Curcumin may be a potential therapeutic alternative for HHBD.